Resistive switching of Cu/Cu2O junction fabricated using simple thermal oxidation at 423 K for memristor application - Ani, Mohd Hanafi; Helmi, F; Herman, Sukreen Hana; Syed Abu Bakar, Syed Noh (IOP Publishing, 2018)
Recently, extensive researches have been done on memristor to replace current memory storage technologies. Study on active layer of memristor mostly involving n-type semiconductor oxide such as TiO2 and ZnO. This paper highlight a simple water vapour oxidation method at 423 K to form Cu/Cu2O electronic junction as a new type of memristor. Cu2O is a p-type semiconductor oxide, was used as the active layer of memristor. Cu/Cu2O/Au memristor was fabricated by thermal oxidation of copper foil, followed by sputtering of gold. Structural, morphological and memristive properties were characterized using XRD, FESEM, and current-voltage, I-V measurement respectively. Its memristivity was indentified by pinch hysteresis loop and measurement of high resistance state (HRS) and low resistance state (LRS) of the sample. The Cu/Cu2O/Au memristor demonstrates comparable performances to previous studies using other methods.